The Diet of Preschool Children in the Mediterranean Countries of the European Union: A Systematic Review - Pereira-da-Silva, L (2016)
This systematic review discusses data on the dietary intake of preschool children living in the Mediterranean countries of the European Union, including the comparison with a Mediterranean-like diet and the association with nutritional status. Specifically, data from the multinational European Identification and Prevention on Dietary and life style induced health effects in children and infants (IDEFICS) study and national studies, such as the Estudo do Padrão Alimentar e de Crescimento Infantil (EPACI) study and Geração XXI cohort in Portugal, ALimentando la SAlud del MAñana (ALSALMA) study in Spain, Étude des Déterminants pré-et postnatals précoces du développement et de la santé de l'ENfant (EDEN) cohort in France, Nutrintake 636 study in Italy, and Growth, Exercise and Nutrition Epidemiological Study in preSchoolers (GENESIS) cohort in Greece, were analyzed. In the majority of countries, young children consumed fruit and vegetables quite frequently, but also consumed sugared beverages and snacks. High energy and high protein intakes mainly from dairy products were found in the majority of countries. The majority of children also consumed excessive sodium intake. Early high prevalence of overweight and obesity was found, and both early consumption of energy-dense foods and overweight seemed to track across toddler and preschool ages. Most children living in the analyzed countries showed low adherence to a Mediterranean-like diet, which in turn was associated with being overweight/obese. Unhealthier diets were associated with lower maternal educational level and parental unemployment. Programs promoting adherence of young children to the traditional Mediterranean diet should be part of a multi-intervention strategy for the prevention and treatment of pediatric overweight and obesity.